1989
DOI: 10.1128/jvi.63.9.3579-3585.1989
|View full text |Cite
|
Sign up to set email alerts
|

Generation and characterization of monoclonal antibodies to the putative CD4-binding domain of human immunodeficiency virus type 1 gp120

Abstract: A panel of seven monoclonal antibodies against the relatively conserved CD4-binding domain on human immunodeficiency virus type 1 (HIV-1) gpl20 was generated by immunizing mice with purified gpl20. These monoclonal antibodies reacted specifically with gpl20 in an enzyme-linked immunosorbent assay and Western blots (immunoblots). By using synthetic peptides as antigens in the immunosorbent assay, the epitopes of these seven monoclonal antibodies were mapped to amino acid residues 423 to 437 of gpl20. Further st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(66 citation statements)
references
References 43 publications
3
63
0
Order By: Relevance
“…The third neutralizing MAb, R53, was the only one in this pilot study that was able to bind all five gp120 antigens from subtype A to subtype E and also showed broad neutralizing activities in Monogram assays despite low potency. Interestingly, previous studies reported that several murine MAbs (28), as well as rat MAbs (27), isolated from gp120 protein immunization were able to prevent gp120 binding to CD4. They mainly bound to a region on aa 430 to 447 of the C4 region, which is now known as part of the Env bridging sheet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third neutralizing MAb, R53, was the only one in this pilot study that was able to bind all five gp120 antigens from subtype A to subtype E and also showed broad neutralizing activities in Monogram assays despite low potency. Interestingly, previous studies reported that several murine MAbs (28), as well as rat MAbs (27), isolated from gp120 protein immunization were able to prevent gp120 binding to CD4. They mainly bound to a region on aa 430 to 447 of the C4 region, which is now known as part of the Env bridging sheet.…”
Section: Discussionmentioning
confidence: 99%
“…3B). Based on the epitope peptide sequence, R53 binds to the bridging sheet of gp120, a rare epitope reported only in a mouse study in the early days of HIV-1 research (27,28). One unique feature of R53 is that it can bind to two discontinuous linear epitopes in the C1 and C4 regions, although there is limited sequence homology between these two peptides.…”
Section: Generation Of Hiv-1 Env-specific Hybridoma Cell Lines From Amentioning
confidence: 99%
“…24-36 h after in-fection, the medium was aspirated and the cells were lysed in a solution of PBS containing 0.5% NP- 40 Epitopes of mAbs used in this study. The epitopes for the V2, V3, and C4 murine mAbs are represented as linear sequences, and were taken from the following sources: BAT085, G3-4, and G3-136 (11); 9284, 110.5, BAT123, and 110.1 (18,29,22, and 60 respectively); G3-42, G3-299, G3-536, G3-519 (28,30). The discontinuous epitopes for the human mAbs were mapped by site-directed mutagenesis.…”
Section: Methodsmentioning
confidence: 99%
“…The CD4 is of particular importance in this regard (Sun et al 1989, Lasky et al 1987). Mutagenesis of both hydrophobic and negatively-charged amino acids in C4 abrogated CD4 binding, indicating that C4 may come into direct contact with CD4 (Olshevky et al 1990, Cordonnier et al 1989).…”
Section: The Cd4-binding Site On Gpi20mentioning
confidence: 99%